Approaches to Learning Traditional Performing Arts in Central Java through a Direct Encounter - Hand, Rachel (Malaysian Journal of Music, 2017)
This paper examines learning approaches that are used by Javanese practitioners of traditional performing arts, including gamelan musicians, dhalang (puppet masters of wayang) and dancers. Based on fieldwork interviews and participant observation in and around Surakarta (Solo), Central Java, I described five learning approaches that have in common a direct encounter with live performing arts, which triggers an immediate learning process. These are learning by ear, simultaneous imitation, rehearsing and performing, exposure and absorption, and learning by association. Each learning approach is described based on the artists’ own accounts of teaching and learning, and supported by pre-existing literature in cognition studies and ethnomusicology. I show that most practitioners have engaged in multiple learning approaches, and also that knowledge of one art form often enables or aids learning in other art forms. Javanese performing arts continue to be popular and sustainable. The learning approaches examined in this paper contribute to such success because they support sites for knowledge transmission through direct encounters with arts as they are performed.